2022
DOI: 10.1017/ice.2022.116
|View full text |Cite
|
Sign up to set email alerts
|

Continued increases in the incidence of healthcare-associated infection (HAI) during the second year of the coronavirus disease 2019 (COVID-19) pandemic

Abstract: National Healthcare Safety Network data were analyzed to assess the impact of COVID-19 on the incidence of healthcare-associated infections during 2021. Standardized infection ratios were significantly higher than those during the pre-pandemic period, particularly during 2021-Q1 and 2021-Q3. HAI incidence was elevated during periods of high COVID-19 hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 9 publications
2
88
0
3
Order By: Relevance
“…A recent study showed that again in 2021, HAI rates increased, though because of data limitations, the authors were unable to correlate HAI rates with COVID-19. 19 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that again in 2021, HAI rates increased, though because of data limitations, the authors were unable to correlate HAI rates with COVID-19. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Nekoliko studija, sprovedenih od početka pandemije COVID-19 u SAD, prikazalo je dramatičan porast infekcije krvi, udružene sa centralnim venskim kateterom (central line associated blood stream infections -CLABSI), dok infekcije urinarnog trakta, udružene sa urinarnim kateterom, nisu pokazale porast 34,35 . Posebno je važno obratiti pažnju na potencijalne uzročnike CLABSI (Staphylococcus coagulasa negative i Staphylococcus aureus sa kože, Candida spp ili gram-negativni patogeni, naročito kod hematoloških pacijenata i pacijenata sa malignitetom).…”
Section: -Indwelling Catheterunclassified
“…Additionally, literature has shown evidence behind daily meetings between hospital leadership and nursing may reduce the CAUTI Standard Infection Rate (SIR) 8 . As critically ill patients began to fill the hospital during the beginning of the COVID-19 pandemic leading to increased IUC use, UHPMC took a multidisciplinary approach to avoid HAIs during the COVID-19 pandemic, including CAUTIs, to create a culture of safety 9 . This approach to HAI prevention during the COVID-19 Pandemic, January 2019 to December 2021, was unique due to combined use of the nurse driven IUC removal protocol, the inclusion of a bedside nursing IUC checklist, and an IUC insertion order set that was created in the electronic medical record (EMR).…”
Section: Introductionmentioning
confidence: 99%